(untitled) (Global Journal of Science Frontier Research, 2012)
Introduction - The large-horned bruchid (Megacerus Fahraeus) is a distinct genus of Bruchinae that merits being the sole member of the tribe Megacerini in the subfamily Bruchinae, with more than 50 species distributed from U.S.A. and Canada to Chile and Argentina (Tera´n and Kingsolver 1977; McNamara 2004). These bruchids have been reported to feed only on the seeds of the morning glory family (Convolvulaceae), with an occasional unconfirmed exception (Center and Johnson 1974; Maes and Kingsolver 2003). Recently the larvae of Megacerus flabelliger were found feeding on seeds of Merremia macrocalyx a convuolvulaceous weed in Venezuela (Johnson and Raimundez-Urrutia, 2008). The weed (M. macrocalyx ) produces fruits with one to four seeds and the bruchid was found to oviposit more frequently on fruits with multiple seeds but only one seed was attacked while in some cases fruits with multiple seeds had eggs. Oviposition occurred most frequently on seeds still on the plant and only eggs of M. flabelliger that were found on seeds of M. macrocalyx (Johnson and Raimundez-Urrutia, 2008).